Guerrilla warfare, flagship project: The spatial politics of Chinese rock in Shenzhen's post-political making of a musical city. Issue 106 (November 2019) - Wang, June; Chen, Li
Abstract: Chinese rock, premised on an identity of dissenters, has always been underground symbolically and literally, in a pattern of spatial fluidity in the city. The introduction of live house might offer a solid material base for political subjectivation of the community. This spatial action of subjectivation in forms of "guerrilla warfare", encounters the growing passion for cultural city making by Municipal Governments. Through the study on transformation of rock space in Shenzhen, we aim to reflect on scholarship on post-political forms of urban governance in China. By probing into the antagonistic actions of the police and the political, we call for attention to territorial strategies used by both sides to consolidate the existing order and to assert a new order respectively. The double side of partition revealed by Rancirian conception of politics of aesthetics allows the governing side to pick and co-opt particular producers and live houses while collapse and/or policing others to re-consolidate spatial orders. Guided by expert-formed consensus, citizen entitlement and citizen participation programmes convert cities to be propaganda sites where state-sanctioned aesthetics is delivered to and experienced by subject-citizens.